The Crop Ontology: a source of standard traits and variables for breeding and agronomy - Arnaud, Elizabeth; Valette, L.; Pietragalla, J.; Laporte, Marie-Angélique; Aubert, C.; Devare, Medha; McLaren, G.; Ribaut, J.M. (2016)
The Crop Ontology is a service of the Integrated Breeding Platform (www.integratedbreeding.net) in collaboration with the CGIAR and partners and under the leadership of Bioversity international. The Crop Ontology (www.cropontology.org) provides harmonized and validated breeders’ trait names, measurement methods, scales for currently 18 crops that are used by the Breeding Management System (BMS). The NextGeneration Breeding Databases developed by Boyce Thompson Institute also embed the Crop Ontology traits. The Crop Ontology contributes to the content of the reference ontologies of the Planteome project (http://www.planteome.org/).